Pemindahan pengetahuan, skil dan kebolehan secara serentak mempengaruhi kesan amalan komunikasi dalam program mentoring : satu kajian kes di UNIMAS - Kamsiah, Hasbullah (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Mentoring programme literature advocates that transfer of knowledge, skill and ability simultaneously influence the relationship between communication practices in mentoring programme individual attitudes and behaviours. From the theoretical evidence, this conceptual framework is developed and tested using qualitative and quantitative research designs. I 00 survey questionnaires have success study been collected from the students who have learned course (Semester 3) at University Malaysia Sarawak. Outcomes of moderated hierarchical multiple regression analysis played showed that transfer of knowledge, skill and ability simultaneously had a partial moderator in between communication practices in mentoring programme with individual attitudes and behaviours (self-leadership and performance graduation). These results can be used to strengthen mentoring theories, improve the research methodology and developed guidelines to be used by practitional to improve the way of delivery information to students.